Hepatitis B Virus Infection in Hemodialisis patient at Prof. DR. W.Z. Johannes Kupang Hospital, East Nusa Tenggara - Irfan, Irfan; Wawomeo, Aris; Kambuno, Norma Tiku (Poltekkes Kemenkes Kupang, 2019)
Background: Hepatitis B or serum hepatitis is a liver infection caused by the hepatitis B virus (VHB) a member of the Hepadnavirus family that can lead to acute and chronic liver inflammation that can continue to be liver cirrhosis or liver cancer. Purpose: This research aims to determine the description of hepatitis B in hemodialysis patients in the Hospital Prof. Dr. W. Z. Johannes Kupang. Methods: This research is a descriptive study. Sampling was done by purposive sampling technique and a total sample of 63 hemodialysis patients. The inclusion criteria of the sample were those had got hemodialysis therapy> 6 months. Data was taken by interview based on a questionnaire to determine the history of hemodialysis, frequency of hemodialysis, history of blood transfusion and examination of blood serum by researchers who were accompanied by laboratory instructors. Results: The results showed that the infection of hepatitis B in hemodialysis patients in hospital Prof. Dr. W.Z. Johannes Kupang from 63 samples obtained 7 positive/reactive HBsAg (11%). Conclusion: History of hemodialysis, frequency of hemodialysis and history of blood transfusion were factors that have the potential to be a source of hepatitis B infection.